2020
DOI: 10.21082/jsdl.v12n2.2018.117-131
|View full text |Cite
|
Sign up to set email alerts
|

Keberlanjutan Inovasi Teknologi Lahan Rawa Pasang Surut : Prospek, Kendala dan Implementasi

Abstract: <p><strong>Abstrak. </strong>Masalah pangan yang dihadapi semakin berat dan kompleksnya ditengah semakin meningkatnya jumlah populasi penduduk dan konversi lahan. Sejak tahun 2018 melalui Program UPSUS PAJALE dan Program SERASI pemerintah di bawah Kementerian Pertanian berupaya meningkatkan produksi pangan, khsusunya beras secara nasional.  Dari luas 20,11 juta hektar lahan rawa pasang surut berpotensi sebagai sumber produksi padi seluas 9,53 juta hektar. Jika 50% saja dari lahan yang cocok t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 1 publication
0
10
0
1
Order By: Relevance
“…Kebutuhan pangan yang meningkat sedangkan lahan-lahan pertanian di Pulau Jawa menurun akibat perubahan penggunaan lahan ke sektor nonpertanian maka lahan pasangsurut menjadi alternatif untuk pengembangan pertanian (Suwanda & Noor, 2014). Dari data BBSDLP (2014) ketersediaan lahan pasang surut mencapai 20,1 juta ha di Indonesia, ketersediaan lahan tersebut menjadi peluang besar untuk menerapkan budidaya jenuh air.…”
Section: Pendahuluanunclassified
“…Kebutuhan pangan yang meningkat sedangkan lahan-lahan pertanian di Pulau Jawa menurun akibat perubahan penggunaan lahan ke sektor nonpertanian maka lahan pasangsurut menjadi alternatif untuk pengembangan pertanian (Suwanda & Noor, 2014). Dari data BBSDLP (2014) ketersediaan lahan pasang surut mencapai 20,1 juta ha di Indonesia, ketersediaan lahan tersebut menjadi peluang besar untuk menerapkan budidaya jenuh air.…”
Section: Pendahuluanunclassified
“…In addition, the potential for horticultural and plantation crops is about 0.519 million ha and 0.124 million ha, respectively (Table 4). Diversification of crop commodities to increase production and income in tidal swamp land is potentially through a Surjan system and proper water management in integrated farming of various food commodities such as rice, secondary crops, vegetables, fruits, coconut, livestock, and fish [12][13][14].…”
Section: Utilizationmentioning
confidence: 99%
“…Climate change causes an increase in air temperature, an increase in sea level, changes in rain patterns, and an increase in the frequency of extreme climate events [30]. Various studies have shown that climate change has caused a decrease in productivity and crop production due to an increase in air temperature, flooding, drought, the intensity of pest and disease attacks, and degradation in the quality of agricultural products [14].…”
Section: Environmentmentioning
confidence: 99%
“…Indonesia has a tidal area of 20.1 million ha [1]. This land is spread across Sumatra, Kalimantan, Sulawesi, and Papua [2]; and is suitable for developing food crops, including soybeans.…”
Section: Introductionmentioning
confidence: 99%